Improving properties of ceramic silicone rubber composites using high vinyl silicone oil. Issue 19 (8th January 2015) - Cao, Erping; Cui, Xiaoqian; Wang, Kai; Li, Yinyin; Guo, Weihong
ABSTRACT Reactive high vinyl silicone oil (HVSO) was selected to prepare the ceramic silicone rubber composites. The effects of HVSO on the mechanical properties and thermal stabilities of ceramic silicone rubber composites were investigated. The structures of the cross‐linked network of silicone rubber with or without HVSO were studied. The intermolecular space of silicone rubber was enlarged, and the cross‐linked point was concentrated by addition of HVSO, which was demonstrated by cross‐linking densities, scanning electron microscope (SEM) images, and dynamic mechanical analysis (DMA). The cross‐linked network model was formed with the slipping of the cross‐linked points along with the silicone rubber chain. Mechanical properties of composites were enhanced by the formation of this cross‐linked network. The tear strength, tensile strength, and elongation at break of the composites were increased by 18.5%, 13.2%, and 37.4% by the adding of 2 phr HVSO, respectively. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41864.